2019
DOI: 10.3390/ijms21010159
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Response to Drought, Rehydration and Re-Dehydration in Potato

Abstract: Potato is an important food crop and its production is susceptible to drought. Drought stress in crop growth is usually multiple- or long-term. In this study, the drought tolerant potato landrace Jancko Sisu Yari was treated with drought stress, rehydration and re-dehydration, and RNA-seq was applied to analyze the characteristics of gene regulation during these treatments. The results showed that drought-responsive genes mainly involved photosynthesis, signal transduction, lipid metabolism, sugar metabolism, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 50 publications
7
51
0
Order By: Relevance
“…In the case of potato, drought was memorized by genes involved in photosynthesis, signal transduction, sugar metabolism, flavonoid metabolism, and the biosynthesis of protease and protease inhibitors, transporters, and transcription factors (Chen et al, 2020). The expression levels of most photosynthesis-related genes during the second drought were higher than during the first drought.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of potato, drought was memorized by genes involved in photosynthesis, signal transduction, sugar metabolism, flavonoid metabolism, and the biosynthesis of protease and protease inhibitors, transporters, and transcription factors (Chen et al, 2020). The expression levels of most photosynthesis-related genes during the second drought were higher than during the first drought.…”
Section: Discussionmentioning
confidence: 99%
“…The first step toward understanding the molecular mechanism of transcriptional memory and its wide application in crop improvement is the identification of stress memory genes. Many dehydration stress memory genes have been identified in Arabidopsis (Ding et al, 2013), Zea mays (Ding et al, 2014;Virlouvet et al, 2018), rice (Li et al, 2019), and potato (Chen et al, 2020). In this study, we identified drought stress memory genes in soybean by microarray analysis using a newly designed 180K DNA chip.…”
Section: Introductionmentioning
confidence: 99%
“…Most photosynthesis genes, such as Psas , Psbs , and Pets , have also been reported to be downregulated in drought-stressed plants, whereas antioxidant enzyme-related genes, including GSTs , PODs , CATs , SODs , and GPXs , as well as genes encoding the respiratory burst oxidase protein (RBOH), have been found to be upregulated [ 46 ]. Other drought-responsive genes involved in transportation ( aquaporin ( PIP ) gene), lipid and sugar metabolisms, wax synthesis, cell wall regulation, and osmotic adjustment have also been reported [ 60 ]. Besides changing the gene expression, drought stress also induces genotoxic alterations, such as DNA damage and mutational events [ 56 ].…”
Section: No and Drought Stressmentioning
confidence: 99%
“…In the memory responses, a subset of genes termed ‘memory genes’ are expressed at highly elevated or reduced levels during subsequent stress conditions. Numerous drought stress memory genes have been identified in Arabidopsis [ 140 ], maize [ 141 , 142 ], rice [ 143 ], potato [ 144 ], and soybean [ 145 ]. In Arabidopsis and soybean, drought-induced memory genes exhibiting elevated levels of transcripts include those involved in ABA-mediated tolerance responses to abiotic stresses, while the drought-repressed memory genes can be classified as light-harvesting- or photosynthesis-related genes [ 140 , 145 ].…”
Section: Epigenetic Regulation Of Aba Signalingmentioning
confidence: 99%